Pengaruh Harga Minyak Dunia dan Belanja Infrastruktur terhadap Keseimbangan Anggaran Pemerintah Indonesia 2015-2024 - Primasari Fitria; Syaputri, Ayu Geby Gisela; Muhammad Bahrul Ulum (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to examine the extent to which World Oil Prices and Infrastructure Spending influence Indonesia's Budget Balance in 2015-2024. The data used in this study are secondary data from 2015-2024. The analysis method used is multiple linear regression analysis. The analysis results indicate that crude oil prices and infrastructure expenditure simultaneously have a significant effect on the Budget Balance, with an F-value of 5.720 and a significance level of 0.013 < 0.015. Partially, infrastructure expenditure has a significant impact on the state budget deficit, with a coefficient of β = 0.456 and p < 0.05, whereas crude oil prices do not have a significant effect (β = -0.106, p = 0.28). This is due to fluctuations in crude oil prices that do not always align with the continuously increasing trend of the state budget deficit each year. Infrastructure expenditure plays a crucial role in supporting economic growth, prompting the government to increase capital spending for development.